Flexural fatigue behavior of hybrid steel-polypropylene fiber reinforced high-strength lightweight aggregate concrete. (9th May 2023) - Cui, Taotao; Ning, Baokuan; Shi, Xinxin; Li, Jinyu
Highlights: HF reinforced HSLC exhibits longer fatigue life and minimum crack propagation rates. The fatigue life equation is established with double logarithmic fatigue equation by considering failure probability. The expression of crack propagation rate with respect to crack length is proposed. Steel fiber can protect lightweight aggregate from damage and extend the crack propagation path. Abstract: Compared with ordinary concrete, high-strength lightweight aggregate concrete (HSLC) can remarkably attenuate self-weight in engineering structures. However, the fatigue performance of ordinary concrete is better than that of HSLC. Herein, the flexural fatigue behavior, including fatigue life and crack propagation process, of hybrid fiber (HF) reinforced HSLC under different stress levels (S = 0.85, 0.80 and 0.75) was investigated. A further analysis on the fatigue life and crack propagation rate of HF reinforced HSLC was also conducted by two-parameter Weibull distribution (2PWD) and Paris law, respectively. The results indicated that the fatigue life of all specimens followed the 2PWD under various stress levels. Compared to the single fiber reinforced HSLC, the HF reinforced HSLC exhibited minimum crack propagation rates, the longest duration of stable development stage and fatigue life. The fatigue life equation was established with double logarithmic fatigue equation by considering failure probability. Furthermore, the expression of crack propagation rate with respect to crack length of each group of specimens was proposed under various stress levels.